Analisis Karakteristik Psikologi Atlet Atletik di Kabupaten Pati Menuju Porprov 2023 - Pratiwi, Adinda Resta Putri; Rumini, Rumini (Universitas Negeri Semarang, 2023)
Psychology has an important role in athletics because it focuses on individual skills. The aim of this research is to analyze the psychological aspects of athletic athletes in Pati Regency towards PORPROV in 2023. This research uses a survey method with a quantitative descriptive approach, sample in this research, namely athletic athletes in Pati Regency who passed the 2023 PORPROV limit. The results of the research showed that the anxiety control category was